How to travel with a salmon and other essays - Eco, Umberto (Vintage, 1998)
How to Travel with a Salmon is a highly engaging collection of what Umberto Eco calls his diario minimo - minimal diaries - after the magazine column in which he began "pursuing the pathways of parody." These essays, written in the late eighties and early nineties, are his playful but unfailingly accurate takes on militarism, computer jargon, Westerns, art criticism, librarians, bureaucrats, meals on airplanes, Amtrak trains, bad coffee, maniacal taxi drivers, express mail, 33-function watches, fax machines and cellular phones, pornography, soccer fans, academia, and - last but definitely not least - the author's own self. How to Travel with a Salmon gives us Umberto Eco's acute vision of the absurdities of modern life.